A combined quantum-chemical and matrix-isolation study on molecular manganese fluorides12. Issue 12 (27th January 2016) - Brosi, Felix; Schlöder, Tobias; Schmidt, Alexei; Beckers, Helmut; Riedel, Sebastian
Abstract : Molecular manganese fluorides were studied in solid neon, argon and fluorine using IR spectroscopy and quantum-chemical calculations at DFT and CCSD(T) levels. Abstract : Molecular manganese fluorides were studied using quantum-chemical calculations at DFT and CCSD(T) levels and experimentally by matrix-isolation techniques. They were prepared by co-deposition of IR-laser ablated elemental manganese or manganese trifluoride with F2 in an excess of Ne, Ar, or N2 or with neat F2 at 5–12 K. New IR bands in the Mn–F stretching region are detected and assigned to matrix-isolated molecular MnF x ( x = 1–3).